PELAKSANAAN PERJANJIAN ASURANSI NELAYAN KECIL DI KABUPATEN BENGKALIS PADA PT ASURANSI JASINDO CABANG PEKANBARU - Devi Satria; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Fishermen are jobs that have a high level of risk, such as bad weather changes and problems that can occur when fishing, and spending money to meet the needs of daily life. The purpose of this study was to study the guarantee of safety for small fishermen through independent fishermen insurance, find out the rights and obligations between the guarantor and small fishermen in obtaining Safety. Fisherman insurance is regulated in the Law on Insurance Number 40 of 2014. Specific regulations on fisheries insurance concerning Law Number 7 of 2016 concerning Protection and Empowerment of Fishermen Insurance for Fishers, Fish Farmers, and Salt Farmers. This study specifically discusses fisherman insurance for small fishing communities. Entering a fisheries insurance agreement is carried out with premium payments paid by small fishermen, without government subsidies / assistance.The research carried out is a sociological legal research that is research that starts with the process of revealing the truth using basic concepts in sociology known as science, and taken from secondary data by processing data from primary legal materials, secondary legal materials, and legal materials tertiary. Research location in Bengkalis Regency, Riau Province. The recommendations used are juridical-sociological, namely research conducted on real situations in the Department of Maritime Affairs and Fisheries (DKP) and local fishermen in the Bengkalis Regency fisheries area.The results of this study regarding the research work agreement by PT Asuransi Jasa Indonesia (Jasindo) Pekanbaru Branch. Implementation of the rights of fishermen in obtaining safety here is less than the awareness and knowledge of the people in Bengkalis Regency to improve the clauses in the policy the Insurer does not give an understanding to small fishermen about things that are excluded in insurance coverage. To the PT Asuransi Jasindo Pekanbaru Branch to explain things that are excluded in the independent fisheries insurance policy, so that the rights of small fishermen can be accounted for according to the Law.Keywords: Fishermen Insurance, PT Asuransi Jasindo, Small Fishermen